A Case Report Improving Quality of Life in Pulmonary Hypertension with Exercise Training Therapy - Ni Putu Frida Baskarani; Cholid Tri Tjahjono (Universitas Brawijaya, 2022)
Pulmonary hypertension is an increase in pulmonary artery pressure >25 mmHg. This causes some disturbing clinical complaints. The most common causes of pulmonary hypertension are idiopathic and congenital heart disease. ASD (Arterial Septal Defect) is a congenital heart disease that occurs in 1.6 per 1000 live births, with a fairly high life expectancy. However, most people with ASD are not aware of a heart problem before the appearance of a clinically significant disorder. Most patients with ASD with complications of pulmonary hypertension will complain of being easily tired, fainting easily and having difficulty carrying out daily activities, even light activities. Most ASD cases apply shunt closure therapy as the main therapy, but not a few ASD cases cannot be shunted closure because it is a contraindication that can lead to more severe complications, especially with complications of chronic pulmonary hypertension. One of the non-medical therapies used to improve the quality of life of patients with pulmonary hypertension is exercise therapy. This therapy provides a variety of physical exercises that aim to increase the strength of respiratory muscles and extremities. From this case, exercise therapy is able to provide a significant improvement in the quality of life of the patient with an increase in the patient's ability to perform physical activities, as evidenced by the increase in distance traveled when doing the six-minute walk test (SMWT).